Auditoria de inventarios de bienes muebles de la Alcaldía Municipal de Caicedonia Valle (2015)
The audit process is carried out to the accounts of property plant and equipment to the movable assets, the Office of the Mayor of Caicedonia Valle, a company of the public sector, which has the function of handling guide and ensure the actions of government, with the intention of improving the living conditions of the inhabitants, ensuring equity of social development, cultural, environmental, economic and public safety. Is the Office Mayor of Caicedonia Valle Mission ensure that their goods are under constant control, but in our particular case is a knowledge of the business, a physical inventory and the necessary procedures to review bailments and papers that support such movable assets, In order to determine reasonable assurance and finally give a recommendation to demonstrate whether this is giving effective compliance to established processes in the Regime of Public accounting.